2010
DOI: 10.4067/s0717-95022010000100022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Clinical Importance of Superficial Arterial Palmar Irrigation and its Variants over 86 Cases

Abstract: SUMMARY:The classic description of the hand's superficial palmar arch is based on the anastomosis among the ulnar and radiopalmar arteries, a branch of the radial artery. However, the arch formation is highly variable regarding the size of the arteries that make it up and due to the existence of branches coming from other arteries and adding up as tributary to it. The objective of this paper is to classify these possible varieties, to define the formation of the arch, the reasons for its variable arrangement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
1
11
0
5
Order By: Relevance
“…[ Ottone N. E, et al, [24] had their unique way of classification into arch and non arch pattern The Existing Arch Type, corresponding to the presence of a proper arch, is found in 58.0 percent of cases. The Non-Arch type was found with a significant frequency, in 42.0 percent of cases.…”
Section: Type Ementioning
confidence: 99%
“…[ Ottone N. E, et al, [24] had their unique way of classification into arch and non arch pattern The Existing Arch Type, corresponding to the presence of a proper arch, is found in 58.0 percent of cases. The Non-Arch type was found with a significant frequency, in 42.0 percent of cases.…”
Section: Type Ementioning
confidence: 99%
“…El uso de la AR como injerto en la revascularización miocárdica, ha generado un interés por el estudio del APS. La ligadura de la AR en pacientes con APS incompleto y APP con alteración de su configuración anatómica, puede traer como consecuencia un proceso isquémico en la mano 9 . Además, al no existir publicaciones en Colombia sobre la expresión morfológica del ¿Cómo citar este artículo?…”
Section: Introductionunclassified
“…[7] According to another classification, the variations of the blood supply to the hand can be classified into an arch type (58%) with ulnarradiopalmar and ulnar-radial subtypes and non-arch type (42%) with dominant ulnar and codominant subtypes. [10] Regardless of the specific variation, it has been proposed that the ulnar artery always takes part in the blood supply of the hand, whether it forms the SPA or not. [10] This study also hypothesised that any variations of the SPA depend entirely on variations observed in the radial artery.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Regardless of the specific variation, it has been proposed that the ulnar artery always takes part in the blood supply of the hand, whether it forms the SPA or not. [10] This study also hypothesised that any variations of the SPA depend entirely on variations observed in the radial artery. [10] The present case report is mostly similar to type II, [9] or the ulnar pattern of the dominant ulnar subtype in the non-arch group.…”
Section: Discussionmentioning
confidence: 99%